Editorial: Epigenetics in Heart Failure Developing: The Orchestra of Etiology and Comorbidities - Berezin, A. E.; Mozos, I.; Petrovic, D.; Березін, Олександр Євгенійович (My University, 2022)
Heart failure (HF) is a multimodal condition associated with a wide range of comorbidities and increased mortality, and remains a major clinical, public health, and economic problem despite significant efforts to improve management of the disease (1). There is resoundingly clear scientific proof of the fact that a number of new cases of HF can be explained by cumulative effects of coexisting diseases involving overlapping genetic and epigenetic mechanisms (2). Current understanding of the basic principles of the molecular machinery underlying occurrence of HF plays a pivotal role in precise care of HF and management of regenerative and translational therapies (3).
Berezin A. E. - orcid.org/0000-0002-0446-3999
Keywords: heart failure; epigenetic mechanisms; co-morbidities; biomarkers; management; diagnosis; prognosis